PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP PENINGKATAN MINAT BELAJAR PESERTA DIDIK - Rahmat Muhajir; Nurhaswin Harisi; Muhajir (STKIP Subang, 2024)
This study aims to examine the influence of technology-based learning media on enhancing student participation. This research is motivated by the rapid advancement of technology and its potential to improve learning effectiveness. A classroom action research design was employed in this study. The sample consisted of seventh-grade students in class 7D of SMP Negeri 33 Makassar. The research instruments used were participation questionnaires and observation sheets. The results indicated a significant difference in student participation before and after the implementation of technology-based learning media. The experimental group showed a higher increase in participation compared to the pre-implementation period. The conclusion of this study is that the use of technology-based learning media can be an effective alternative to enhance student participation in the learning process.